Environmental Engineering of Electric Vehicle Infrastructure and Technology in Supporting Green Tourism and Energy - Dwipayana, Arif Devi; Ahmad, Rahmat; Wiguna, I Wayan Yudi Martha (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
The use of technology to reduce carbon emissions that support green tourism is electric vehicles, one of its advantages is that it does not produce exhaust emissions that can pollute the environment. The purpose of this research is to see the readiness of the Bali Provincial Government in preparing the engineering of the use of electric vehicles, especially infrastructure and technology to support green tourism and green energy. this research method is carried out using literacy study data collection techniques and data sources with secondary data types. The discussion in this study can be described qualitatively based on the results of data processing that has been collected previously. The implementation of the regulation has produced results but does not have a significant impact, because it only focuses on tourism areas in Denpasar City and Badung Regency, the main infrastructure in supporting electric vehicles is the availability of SPKLU in tourism areas, the use of electric buses can be further expanded and the route increased, thus increasing tourist interest in using these services. Further research can be carried out on how much exhaust emissions and air pollution decrease in tourism areas.